Organizational Change: A Review of Theory and Research in the 1990s - Armenakis, Achilles A.; Bedeian, Arthur G. (Journal of Management, 1999)
This review selectively examines the theoretical and empirical organizational change literature over the past nine years (1990–early 1998). Four research themes or issues common to all change efforts are discussed: (a) content issues, which largely focus on the substance of contemporary organizational changes; (b) contextual issues, which principally focus on forces or conditions existing in an organization’s external and internal environments; (c) process issues, which address actions undertaken during the enactment of an intended change, and (d) criterion issues, which deal with outcomes commonly assessed in organizational change efforts. Research dealing with monitoring affective and behavioral reactions to change is also reviewed. In closing, general observations and suggestions for future research are offered and it is concluded that the organizational change literature continues to be responsive to the dynamics of contemporary workplace demands.